2013
DOI: 10.4236/ojmetal.2013.32a1009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Immobilization in Artificially Contaminated Soils Using Some Local Amendments

Abstract: Three alluvial soil samples with different textures were artificially polluted with chloride solutions of Cd, Pb, Co and chromate solution for Cr. The aqua-regia extracted concentration ranges in the artificially polluted soils were 1134 - 1489 mg·kg-1 for Pb, 854 - 938 mg·kg-1 for Cr, 166 - 346 mg·kg-<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Higher pH was observed in soils that received both amendments and heavy metals than soils that received only heavy metals as shown in Table 3. The results agree with the findings of [29], [30] who observed that application of farmyard manure caused an increase in soil pH and [17] who obtained significant effect of amendment on soil pH. Lead combined with poultry manure had the highest significant (P<0.05) effect on pH followed by zinc plus poultry manure that was significantly different (P<0.05) but not different from copper plus poultry manure and zinc mixed with cocoa pod.…”
Section: Chemical Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…Higher pH was observed in soils that received both amendments and heavy metals than soils that received only heavy metals as shown in Table 3. The results agree with the findings of [29], [30] who observed that application of farmyard manure caused an increase in soil pH and [17] who obtained significant effect of amendment on soil pH. Lead combined with poultry manure had the highest significant (P<0.05) effect on pH followed by zinc plus poultry manure that was significantly different (P<0.05) but not different from copper plus poultry manure and zinc mixed with cocoa pod.…”
Section: Chemical Propertiessupporting
confidence: 91%
“…The metal salts were thoroughly mixed with the soils to homogenize the distribution of the applied heavy metals and allowed to incubate for thirty days. Each soil was wetted daily with 80 ml of distilled water throughout the incubation period at room temperature to mimic natural field condition as stipulated by [17].…”
Section: Methodsmentioning
confidence: 99%
“…A soluble form of phosphorus such as phosphoric acid or triple super phosphate which drives down the soil pH may be used to convert as much Pb as possible to pyromorphite. This may require the addition of excess P, which has potential negative consequences including mobilisation of Sb [19,71] and potential eutrophication [16,72].…”
Section: The Application Of Phosphate For Chemical Stabilisation Of Smentioning
confidence: 99%
“…Therefore, the compliance to the SQD requirements in these conditions indicated the adequacy of the leachates also for the column test, applied in the SQD. As performed in other studies (Abdel-Kader et al, 2013), the retention rate, indicating the rate of retained ions in the system after leaching test in the presence of PC, was calculated using the formula:…”
Section: Environmental Impact Evaluationmentioning
confidence: 99%